Diagnosis of Protein C Deficiency in Patients on Oral Anticoagulant Treatment: Comparison of Three Different Functional Protein C Assays - Pabinger, I; Kyrle, P A; Speiser, W; Stoffels, U; Jung, M; Lechner, K (Thrombosis and Haemostasis, 1990)
The efficacy of three different protein C activity assays and of protein C antigen determination for the diagnosis of protein C deficiency was studied in 13 protein C deficient patients (11 with type I, 2 with type II deficiency) and in 51 presumably nondeficient patients (control group), both groups being on oral anticoagulant (OAC) treatment. For protein C activity measurement (1) the assay according to Francis (slightly modified) with thrombin activation and measurement of activated protein C in the aPTT system, (2) an assay using Protac activation and chromogenic substrate (Protac-CS) and (3) an assay using Protac activation and the aPTT system (Protac-PTT) were used. Protein C antigen was determined by Laurcll immunoelec-trophoresis. The three activity assays gave different results, with the highest values obtained by the Protac-CS assay and the lowest values by the Protac-PTT assay. The Francis assay gave intermediate results.Protein C activity and antigen values were significantly lower in protein C deficient patients compared to the control group. Protein C activity tests had a higher discriminative power than the antigen determination. After taking into account the intensity of treatment, by the Francis assay all deficient and non-deficient patients were correctly classified, by the Protac-CS and the Protac-PTT assay 2 and 4 patients, respectively, were misclas-sified and by the antigen assay 8 patients were misclassified. Calculation of the ratios of protein C activity to factor II activity was of high discriminative power.We conclude that for diagnosis of protein C deficiency protein C activity tests are superior to antigen determination not only in type II but also in type I deficient patients. Certain statistical procedures can further improve the discrimination between deficient and non-deficient patients.